Culture and Gender in the Danelaw: Scandinavian and Anglo-Scandinavian Brooches - Kershaw, Jane F. (Viking and Medieval Scandinavia, 2009)
Abstract Recent metal-detecting in areas of northern and eastern England has brought to light hundreds of Viking-Age brooches decorated in Scandinavian styles. While some objects are likely to be products of Anglo-Saxon and Scandinavian interaction, others are diagnostically Scandinavian and may have been imported from the Scandinavian homelands. The following considers the distribution of these items within England, together with their chronology and status. It suggests that such pieces were worn to express Scandinavian cultural affiliation within the Danelaw. Given the status of these brooches as female dress accessories, it proposes that women in particular had a key role in promoting a Scandinavian colonial identity. In this context, this paper contributes to increasing scholarly interest in the value of material form, decoration, and consumption for negotiating identity in the Danelaw.